in vivo Evaluation of Noxious Stimulus Induced Pain and Inflammation in Mice and Rats Using Methanolic Extract of Galphimia glauca Leaf - Rao Garige, Baba Shankar; Keshetti, Srisailam; Rao Vattikuti, Uma Maheshwara (Asian Journal of Chemistry, 2016)
This study assesses the analgesic and anti-inflammatory properties of methanolic extract of Galphimia glauca leaf using in vivo models. The dose range of 100, 200 and 400 mg/kg b.w was administered orally for assessing analgesic and anti-inflammatory activity respectively. Further studies were conducted for determining the involvement of central and peripheral receptor actions in the analgesic activity of the extract by pre-challenging it with naloxone and acetic acid respectively. The LD50 of the extract was found to be > 2000 mg/kg b.w. The leaf extract at 400 mg/kg dose exhibited significant (P £ 0.001) and dose-dependent analgesic activity. It also exhibited central and peripheral analgesic actions when treated with naloxone and acetic acid respectively. However, the extract of leaf has shown anti-inflammatory activity, which is not comparable to that of standard drug. The results revealed that the methanolic extract of Galphimia glauca leaf has potential in terms of analgesic properties.